UPAYA HUKUM PEMBEBASAN TANAH PUSAKA TINGGI UNTUK PENGADAAN JALAN TOL DI SUMATERA BARAT - Dwi Putra, Diki Okta (Jurnal Hukum Ius Publicum, 2024)
In 2018 the government started the construction of the padang-pekanbaru toll road project which is targeted to be operational in 2023, which is part of the trans-Sumatra toll road development project initiated by the government. but until now at the end of 2021 the construction process has not yet reached 50 percent and the end of 2024 is still 85 percent past the target limit. One of the most important factors hampering the construction of this toll road is the problem of land acquisition in areas that are mostly high heirloom land. The method in this writing uses normative juridical. The problem in this paper is how the process of land acquisition if the object is high heirloom land in West Sumatra and what are the legal efforts of the government to acquire high heirloom land in West Sumatra which are considered not detrimental to the rights of indigenous peoples to high heirloom land. high heirloom land can legally be sold on the grounds of public interest, but this is different from the customary law in West Sumatra where this high heirloom land cannot be sold. The legal efforts of the government itself continue to follow the applicable laws and regulations, namely Law Number 2 of 2012 concerning Land Acquisition for Development for the Public Interest, but on the other hand the government also considers and pays attention to community requests in accordance with the provisions of their customary law.